School shootings and student performance - Panu Poutvaara; Olli Ropponen (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper, we study how high school students reacted to the shocking news of a school shooting. The shooting coincided with national high-school matriculation exams. As there were exams both before and after the shooting, we can use a difference-in-differences analysis to uncover how the school shooting affected the test scores compared to previous years. We find that the average performance of young men declined due to the school shooting, whereas we do not observe a similar pattern for women.
Keywords: C21; J16; I19; 330; school shootings; school performance; shocking news; gender differences; treatment effect models; Bildungsabschluss; Allgemeinbildende Schule; Gewalt; Schock; Schüler; Geschlecht; Finnland